2022
DOI: 10.1007/s12519-022-00536-2
|View full text |Cite
|
Sign up to set email alerts
|

Fish oil-containing lipid emulsions prevention on parenteral nutrition-associated cholestasis in very low birth weight infants: a meta-analysis

Abstract: Background The effect of fish oil-containing lipid emulsions on preventing parenteral nutrition-associated cholestasis (PNAC) in very low birth weight (VLBW) infants is not known. Thus, we conducted a meta-analysis to identify any prevention effect. Methods PubMed, EMBASE, and CENTRAL were searched up to 26 January 2021 for studies related to the preventive effect of fish oil-containing lipid emulsions and fish oil-free lipid emulsions on cholestasis in VL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 41 publications
0
8
0
1
Order By: Relevance
“…In public administration, the Governor as the provincial leader is a public official who has a political office, he hopes that in the future there will be conformity for regional autonomy that cannot be generalized to each region due to differences in cultural customs and geographical location in each region. In this case, regional income has a relationship with various physical and socioeconomic variables is to identify which variable has the most influence on regional revenue receipts (Zou et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In public administration, the Governor as the provincial leader is a public official who has a political office, he hopes that in the future there will be conformity for regional autonomy that cannot be generalized to each region due to differences in cultural customs and geographical location in each region. In this case, regional income has a relationship with various physical and socioeconomic variables is to identify which variable has the most influence on regional revenue receipts (Zou et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…A range of meta-analyses have found compelling clinical benefits for the use of FO in PN from multiple RCTs, which includes the recently published Canadian Critical Care Nutrition guidelines [4 ▪▪ ,31 ▪▪ ,32] (see Table 2 for summary of recent meta-analysis publications on omega-3 ILE sparing trials). To exemplify this, results of the largest meta-analysis [39 ▪▪ ], including 49 RCTs and 3641 patients, showed the use of n-3 PUFAs was associated with 40% fewer infections ( P < 0.00001), approximately 2 days’ shorter hospital stay ( P < 0.00001), about 2 days shorter ICU stay ( P = 0.01), and sepsis was reduced by 56% ( P = 0.0004) [33]. Further cost-effectiveness evaluation using data from this meta-analysis demonstrated that FO-containing ILE reduced costs in the United States and a range of European countries (see data summarized in Figs.…”
Section: Impact Of Lipid Formulation On Clinical Outcomes: Does It Ma...mentioning
confidence: 99%
“…An added benefit of the omega-3 fatty acid ILEs found in FO is that they increase learning, memory, cognitive well being, and blood flow to the brain [38 ▪ ]. It is also clearly proven that pure FO-LE in PN reduce, and in fact can reverse, the occurrence of cholestasis in very low birth weight and preterm infants [5 ▪▪ ,39 ▪▪ ,40 ▪ ,41].…”
Section: Impact Of Lipid Formulation On Clinical Outcomes: Does It Ma...mentioning
confidence: 99%
“…Hasilnya menunjukkan bahwa pemberian emulsi lemak mengandung sh oil dapat menurunkan kejadian PNAC (parenteral nutrition associated cholestasis) secara bermakna (p=0,002) dan hasil analisis subgrup menunjukkan bahwa penurunan PNAC lebih baik pada subjek yang mendapat emulsi lemak tidak lebih dari 14 hari dan pada bayi yang beratnya di bawah 1.000 gram. 22 Selain karbohidrat, protein, dan lemak yang merupakan sumber energi utama bayi dan anak, dibutuhkan juga vitamin dan mineral. Vitamin dan mineral dibutuhkan untuk mempertahankan integritas dan fungsi sistem imun bayi dan anak.…”
Section: Continuing Professional Developmentunclassified